Phytoestrogens in Soybean and Precocious Pubertal Development: Causality or Casuality? - Calcaterra, Valeria; Regalbuto, Corrado; Mercurio, Giuseppe; Tenuta, Elisavietta; Verduci, Elvira; Zuccotti, Gianvincenzo; Fabiano, Valentina (International Journal of Pediatrics and Child Health, 2021)
Introduction: Data on the effects of phytoestrogens soy exposure on pubertal timing have been equivocal. We reported a case of a girl who had eaten only soy and derivatives for her first 9 years of life and presented clinical manifestation of precocious pubertal development. Case presentation: A caucasian female infant, after 40 days of exclusive breastfeeding, was introduced to soy formula due to suspected milk protein allergy. Since then, the patient ate soy beverage and soy-based foods exclusively. At the age of 7 years and 9 months, the girl showed premature thelarche and pubarche. Advanced skeletal age was detected. Peak of LH after GnRH stimulation test was <5 mU/ml. At the age of 9 years, Tanner pubertal stage was 3, with a further advanced bone age; initial pubertal growth spurt and estrogenization of the external genitalia were also revealed. GnRH stimulation test produced a peak of LH 3.7 mU/ml. Other hormonal parameters resulted within normality ranges. Suspension of the intake of soy-based Fozods was adopted. After 6- 12 months of follow-up, the physical examination and lab results were unchanged compared to the previous investigation, without progression of bone age. A slow progression of puberty was recorded. The patient had menarche at the age of 11 years and 1 month. Conclusion: This case suggests that soybean compounds may play a key role, as an environmental factor, in the precocious pubertal development. Special attention to diet is mandatory in pediatric age in order to preserve a physiological development and future health.